The Role of Water in ATP Hydrolysis Energy Transduction by Protein Machinery - Suzuki, Makoto; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book introduces recent progress in biological energetics from ATP hydrolysis to molecular machineries. The role of water is now recognized to be essential in biological molecular energetics. Although energetics is a rather distant field to many biologists, any working models for protein machineries such as protein motors, transporters, and other enzymes must be consistent with their energetics. Therefore, the book is intended to help scientists build systematic models of biomolecular functions based on three categories: (1) ATP hydrolysis reactions including ionic hydration and protonation-deprotonation of biomolecules, (2) protein-ligand/protein-protein interactions including hydration-dehydration processes, and (3) functioning mechanisms of protein machineries based on water functions. .
Part I: Basis of ATP Hydrolysis Reaction -- 1. Free Energy Analyses for the ATP Hydrolysis in Aqueous Solution by Large-Scale QM/MM Simulations Combined with a Theory of Solutions -- 2. Role of Metal Ion Binding and Protonation in ATP Hydrolysis Energetics -- 3. Spatial Distribution of Ionic Hydration Energy and Hyper-mobile Water -- 4. Theoretical studies of strong attractive interaction between macro-anions mediated by multivalent metal cations and related association behavior: Effective interaction between ATP binding proteins can be regulated by hydrolysis -- 5. Statistical mechanical integral equation approach to reveal the solvation effect on hydrolysis free energy of ATP and its analogue -- 6. A Solvent Model of Nucleotide-protein interaction - Partition coefficients of phosphates in solvent-water mixtures- -- Part II: Basis of Protein-Ligand and Protein-Protein Interactions -- 7. Energetics of myosin-ATP hydrolysis by calorimetry -- 8. Orchestrated electrostatic interactions among myosin, actin, ATP, and water -- 9. Protonation/deprotonation of proteins by neutron diffraction structure analysis -- 10. All-atom analysis of free energy of protein solvation through molecular simulation and solution theory -- 11. Uni-directional propagation of structural changes in actin filaments -- 12. Functional mechanisms of ABC transporters as revealed by molecular simulations -- 13. Statistical thermodynamics on the binding of biomolecules -- Part III: Functioning Mechanisms of Protein Machinery -- 14. Ratchet model of motor proteins and its energetics -- 15. Single Molecule Analysis of Actomyosin in the Presence of Osmolyte -- 16. Novel intermolecular surface force unveils the driving force of actomyosin system -- 17. Extremophilic enzymes related to energy conversion -- 18. Functioning mechanism of ATP-driven proteins inferred on the basis of water-entropy effect -- 19. Controlling the motility of ATP-driven molecular motors using high hydrostatic pressure -- 20. Modulation of the sliding movement of myosin-driven actin filaments associated with their distortion: The effect of ATP, ADP, and inorganic phosphate.
Keywords: Physical chemistry; Proteins .; Biophysics; Physical Chemistry; Protein Biochemistry; Biophysics